Hurst's the heart : manual of cardiology - O'Rourke, Robert A (McGraw-Hill, 2001)
*A portable handbook providing on-the-spot answers to heart problems based on the new tenth edition of Hurst\'s The Heart *Focuses on treatment with emphasis on drug therapy *Can be used as a stand-alone or when the larger reference is not available
Keywords: Hypertension; hypertenze; nemoci srdce; diagnostika; angiologie; Heart Diseases; DIAGNÓZA KARDIOVASKULÁRNÍ